Electrode and lithium-ion secondary battery
By forming a specific proportion of sulfur-modified polyacrylonitrile and lithium titanium oxide active material layer on the current collector of the lithium ion secondary battery, the problem of lowering the capacitance and insufficient high-temperature stability during high-speed charging and discharge of the lithium ion secondary battery is solved, and the effects of high-capacitance and high-temperature stability are achieved.
Patent Information
- Application Number
- CN202180041749.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-06-12
- Filing Date
- 2021-06-02
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2041-06-02
AI Technical Summary
The existing lithium-ion secondary batteries have reduced capacity during high-speed charging and discharge, and have insufficient high-temperature stability.
By forming an active material layer containing a specific proportion of sulfur-modified polyacrylonitrile and lithium titanium oxide on the current collector, the average secondary particle size of the sulfur-modified polyacrylonitrile is greater than the average secondary particle size of the lithium titanium oxide, and the content of sulfur-modified polyacrylonitrile and lithium titanium oxide is controlled respectively in the active material layer.
It achieves high capacitance during high-speed charging and discharging, and maintains excellent stability under high temperature conditions.
Smart Images

Figure BDA0003990099000000281 
Figure BDA0003990099000000291 
Figure HDA0003990099010000011
Abstract
Description
Technical Field
[0001] The present invention relates to an electrode containing sulfur-modified polyacrylonitrile and lithium titanium oxide as electrode active materials, and a lithium ion secondary battery including the electrode. Background Art
[0002] Compared with conventional nickel-metal hydride secondary batteries, lithium-ion secondary batteries have higher cell voltage and higher energy density. Therefore, in addition to mobile devices such as smartphones, they are also increasingly used in electronic devices such as hybrid vehicles, electric vehicles, stationary batteries, and laptop computers. However, there are issues such as high capacity, high output, long life, improved safety, and low cost, and the development of electrode materials, electrolytes, and separators is being actively carried out.
[0003] For example, Patent Document 1 proposes a lithium-ion secondary battery, in which at least one selected from lithium nickel cobalt manganese composite oxide, spinel lithium manganese nickel composite oxide, lithium phosphorus oxide with olivine structure, lithium cobalt oxide, lithium nickel cobalt composite oxide and lithium manganese composite oxide is used in the positive electrode, and lithium titanium oxide is used in the negative electrode.
[0004] In addition, Patent Document 2 discloses a lithium-ion secondary battery in which lithium iron phosphate is used as the positive electrode and a carbon-coated LTO electrode is used as the negative electrode (an electrode using the following particles, in which polyacrylonitrile is formed on the surface and inside of the lithium titanium oxide particles by emulsion polymerization of acrylonitrile monomer, and then carbonization treatment is performed to coat the surface of the lithium titanium oxide particles with carbon).
[0005] Patent Document 3 discloses a lithium ion secondary battery in which sulfur-modified polyacrylonitrile is used as a positive electrode and metal lithium foil is used as a negative electrode.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent No. 3769291
[0009] Patent Document 2: Japanese Patent Application No. 2019-521488
[0010] Patent Document 3: International Publication No. 2010 / 044437 Summary of the invention
[0011] Problems to be solved by the invention
[0012] Conventional lithium-ion secondary batteries have the following problem: when high-speed charging and discharging is performed, the charge and discharge capacity is reduced. Therefore, the object of the present invention is to provide an electrode having a high capacity obtained during high-speed charging and discharging and excellent high-temperature stability. In addition, the object of the present invention is to provide a lithium-ion secondary battery having the electrode as a positive electrode or a negative electrode.
[0013] Means for solving problems
[0014] The present inventors have conducted intensive studies and have found that the above-mentioned problems can be solved by forming an active material layer containing sulfur-modified polyacrylonitrile and lithium titanium oxide in a specific ratio and having average secondary particle sizes satisfying a specific relationship, thereby completing the present invention.
[0015] That is, the present invention is an electrode having an active material layer formed on a current collector, wherein the active material layer contains sulfur-modified polyacrylonitrile and lithium titanium oxide, wherein the average secondary particle size of the sulfur-modified polyacrylonitrile is larger than the average secondary particle size of the lithium titanium oxide, and the content of the sulfur-modified polyacrylonitrile in the active material layer is 5% to 85% by mass, and the content of the lithium titanium oxide in the active material layer is 5% to 85% by mass.
[0016] In the electrode of the present invention, the sulfur-modified polyacrylonitrile preferably has an average secondary particle size of 0.1 μm to 50 μm.
[0017] In the electrode of the present invention, the average secondary particle size of the lithium titanium oxide is preferably 0.05 μm to 30 μm.
[0018] The present invention is also directed to a lithium ion secondary battery comprising a positive electrode, a negative electrode, and a non-aqueous electrolyte containing a lithium salt, wherein the positive electrode or the negative electrode is the above-mentioned electrode.
[0019] In the lithium ion secondary battery of the present invention, the nonaqueous electrolyte containing a lithium salt is preferably a liquid nonaqueous electrolyte, a polymer gel nonaqueous electrolyte, a polymer nonaqueous electrolyte, a complex hydride solid electrolyte or an inorganic solid electrolyte.
[0020] In the lithium ion secondary battery of the present invention, the nonaqueous electrolyte containing the lithium salt is preferably a liquid nonaqueous electrolyte, and the liquid nonaqueous electrolyte contains a cyclic carbonate compound.
[0021] In the lithium ion secondary battery of the present invention, it is more preferable that the liquid nonaqueous electrolyte further contains a chain carbonate compound.
[0022] In the lithium ion secondary battery of the present invention, the nonaqueous electrolyte containing a lithium salt is preferably an inorganic solid electrolyte, and the inorganic solid electrolyte is preferably a sulfide solid electrolyte or an oxide solid electrolyte.
[0023] Effects of the Invention
[0024] According to the present invention, it is possible to provide a lithium ion secondary battery having a high capacity obtained during high-rate charge and discharge and excellent high-temperature stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a longitudinal cross-sectional view schematically showing an example of the structure of a coin-type battery of the lithium ion secondary battery of the present invention.
[0026] Figure 2 This is a schematic diagram showing the basic structure of a cylindrical battery of the lithium ion secondary battery of the present invention.
[0027] Figure 3 This is a perspective view showing the internal structure of a cylindrical battery of the lithium ion secondary battery of the present invention as a cross section.
[0028] Figure 4 This is an exploded perspective view schematically showing a stacked electrode group inside a stacked battery of a lithium ion secondary battery of the present invention.
[0029] Figure 5 This is an exploded perspective view schematically showing a stacked battery of the lithium ion secondary battery of the present invention.
[0030] Figure 6 It is a plan view schematically showing the appearance of a stacked-type battery of the lithium-ion secondary battery of the present invention. DETAILED DESCRIPTION
[0031] Hereinafter, the electrode and the lithium ion secondary battery of the present invention will be described in detail based on preferred embodiments.
[0032] The electrode of the present invention is characterized in that an active material layer containing sulfur-modified polyacrylonitrile and lithium titanium oxide is formed on a current collector.
[0033] <Sulfur-modified polyacrylonitrile>
[0034] Sulfur-modified polyacrylonitrile (hereinafter sometimes referred to as "SPAN") can be produced by mixing a polyacrylonitrile compound with sulfur and performing a heat treatment at 250° C. to 600° C. in a non-oxidizing atmosphere to modify the polyacrylonitrile compound. The non-oxidizing atmosphere refers to an atmosphere having an oxygen concentration of less than 5% by volume, preferably less than 2% by volume, and more preferably substantially free of oxygen, and examples thereof include an inert gas atmosphere such as nitrogen, helium, argon, and a sulfur gas atmosphere.
[0035] Alternatively, SPAN can be produced by mixing a polyacrylonitrile compound with sulfur and then adding other active materials and a conductive additive.
[0036] The polyacrylonitrile compound may be a homopolymer of acrylonitrile or a copolymer of acrylonitrile and other monomers. If the content of acrylonitrile in the polyacrylonitrile compound is reduced, the high capacity of the battery brought by the active material cannot be achieved, and the battery performance is reduced. From this point of view, the content of acrylonitrile in the copolymer of acrylonitrile and other monomers is preferably at least 90% by mass, and more preferably a polyacrylonitrile homopolymer. As other monomers, for example, acrylic acid, vinyl acetate, N-vinyl formamide, N, N'-methylenebis (acrylamide) can be listed.
[0037] SPAN is preferably prepared into a desired particle size by a method such as pulverization or granulation. The pulverization may be dry pulverization in a gas or wet pulverization in a liquid such as water. Examples of industrial pulverization methods include ball milling, roller milling, turbine milling, jet milling, cyclone milling, hammer milling, pin milling, rotary milling, vibration milling, planetary milling, grinding, and bead milling.
[0038] The crushed SPAN is preferably further classified. The classification method is not particularly limited, and can be dry classification methods such as gravity classification, inertial classification, centrifugal classification, etc.; wet classification methods such as sedimentation classification, mechanical classification, hydraulic classification, etc.; classification methods such as screening classification methods using a screen such as vibration screening and in-plane motion screening. Among them, the screening classification method is preferred.
[0039] By carrying out the pulverization and classification steps, SPAN having a particle size suitable for the electrode of the present invention can be efficiently produced.
[0040] As SPAN, SPAN containing primary particles, SPAN containing secondary particles as aggregates of primary particles, or SPAN containing both primary particles and secondary particles can be used. The average secondary particle size (D50) of SPAN is preferably 50 μm or less, more preferably 30 μm or less, and further preferably 20 μm or less. On the other hand, if the average secondary particle size of SPAN is too small, the operability deteriorates, and side reactions are easily generated as the specific surface area of the particles increases, which has an adverse effect on the charge and discharge stability of the lithium-ion secondary battery. Therefore, the average secondary particle size (D50) of SPAN is preferably 0.1 μm or more, more preferably 0.5 μm or more, and further preferably 1 μm or more.
[0041] The average secondary particle size of SPAN is the 50% particle size measured by the laser diffraction light scattering method. In the laser diffraction light scattering method, the particle size is a volume-based diameter, and the secondary particle size of SPAN is measured. When the average secondary particle size of SPAN is measured by the laser diffraction light scattering method, SPAN is dispersed in a dispersion medium such as water or alcohol for measurement.
[0042] In the present invention, the shape of SPAN may be fibrous. When using fibrous SPAN, the preferred average fiber diameter is 0.05 μm or more and 10 μm or less. The smaller the fiber diameter, the more preferred, but with regard to polyacrylonitrile, which is the raw material of SPAN, it is difficult to obtain industrial products of polyacrylonitrile having an average fiber diameter of less than 0.05 μm. In addition, when the average fiber diameter is greater than 10 μm, a large charge and discharge capacity may not be obtained. From the viewpoint of obtaining a larger charge and discharge capacity and the viewpoint of easy availability, the average fiber diameter of the fibrous SPAN is preferably 0.1 μm to 5 μm, and more preferably 0.15 μm to 2 μm.
[0043] When the aspect ratio of the fibrous SPAN is represented by the ratio of fiber length / fiber diameter, the average aspect ratio of the fibrous SPAN is preferably 3 or more, and more preferably 5 or more. When the aspect ratio becomes larger, a large charge and discharge capacity can be obtained, so it is preferred that the fiber length is larger, but if the fiber length is too large, the surface of the active material layer containing SPAN is sometimes not smooth. The average fiber length of the fibrous SPAN is preferably 300 μm or less, and more preferably 150 μm or less. From the same point of view, the average aspect ratio of the fibrous SPAN is preferably 5000 or less, and more preferably 1000 or less. The fiber length and fiber diameter of the fibrous SPAN can be obtained from a scanning electron microscope image (SEM image). The fiber length indicates the length of the fiber, and the fiber diameter indicates the diameter of the circle when the cross section orthogonal to the longitudinal direction of the fiber is circular, and indicates the average of the short diameter and the long diameter of the cross section when the cross section is not circular. The measurement of the fiber diameter in a fibrous SPAN can be performed at any position.
[0044] The average aspect ratio of the fibrous SPAN is a value calculated by dividing the average fiber length by the average fiber diameter. The average fiber length and the average fiber diameter represent the values obtained by arithmetic averaging the fiber diameters and fiber lengths measured from SEM images of 10 or more fibrous SPANs.
[0045] The sulfur content in SPAN is preferably 30% by mass to 45% by mass, and more preferably 35% by mass to 43% by mass, in order to obtain a large charge and discharge capacity and excellent cycle characteristics.
[0046] In addition, in this specification, the sulfur content of SPAN represents the value calculated from the result of elemental analysis using a CHN analysis device (for example, vario MICRO cube manufactured by Elementar) capable of analyzing sulfur and oxygen.
[0047] In the active material layer containing SPAN and lithium titanium oxide, the content of SPAN is in the range of 5 mass % to 85 mass %, preferably in the range of 10 mass % to 80 mass %. When the content of SPAN exceeds 85 mass %, the rate characteristics of the lithium ion secondary battery are greatly reduced. On the other hand, when the content of SPAN is less than 5 mass %, the discharge capacity of the lithium ion secondary battery during high-speed charging is reduced.
[0048] <Lithium Titanium Oxide>
[0049] Examples of the lithium titanium oxide include compounds represented by the following general formula (1).
[0050] Li a Ti b O c M d (1)
[0051] (In the formula, M represents one or a mixture of two or more selected from Zr, B, Sn, S, Be, Ge and Zn, and a, b, c and d represent 0.5≤a≤5, 1≤b≤5, 2≤c≤12, and 0≤d<0.1, respectively.)
[0052] Examples of lithium titanium oxides suitable for the electrode of the present invention include spinel structure lithium titanium oxides and ramsdellite structure lithium titanium oxides. Examples of spinel structure lithium titanium oxides include Li 4+ e Ti5O 12 Examples of ramsdellite structure lithium titanium oxides include Li 2+e Ti3O7、Li 1+f Ti2O4、Li 1.1+f Ti 1.8 O4、Li 1.07+ f Ti 1.86 O4, etc. Furthermore, e and f represent -1≤e≤1 and 0≤f≤1, respectively.
[0053] In the electrode of the present invention, spinel structure lithium titanium oxide is preferred because it has little volume change during charge.
[0054] As the lithium titanium oxide, lithium titanium oxide including primary particles, lithium titanium oxide including secondary particles which are aggregates of primary particles, or lithium titanium oxide including both primary particles and secondary particles can be used.
[0055] The average primary particle size (D50) of lithium titanium oxide is preferably 0.01 μm or more and 10 μm or less, preferably 0.05 μm or more and 1 μm or less. Lithium titanium oxide having an average primary particle size of less than 0.01 μm is difficult to manufacture. On the other hand, if the average primary particle size of lithium titanium oxide exceeds 10 μm, the surface roughness of the electrode becomes larger, the surface area becomes smaller, the affinity of the electrode to the non-aqueous electrolyte is reduced, and the discharge cycle life is sometimes shortened.
[0056] The average primary particle size of the lithium titanium oxide refers to a value obtained by arithmetic averaging the major diameters of 10 or more lithium titanium oxides measured using a SEM image.
[0057] The average secondary particle size (D50) of lithium titanium oxide is preferably 0.05 μm or more and 30 μm or less, more preferably 0.5 μm or more and 10 μm or less. If the average secondary particle size of lithium titanium oxide is less than 0.05 μm, it is difficult to handle, a large amount of adhesive is required, and the aggregation of primary particles becomes significant, the affinity of the electrode to the non-aqueous electrolyte is reduced, the resistance of the electrode interface is increased, and the output characteristics and charge-discharge cycle characteristics of the lithium ion secondary battery are sometimes reduced. On the other hand, if the average secondary particle size of lithium titanium oxide exceeds 30 μm, the diffusion resistance increases, and sometimes the output characteristics and charge-discharge cycle characteristics are adversely affected.
[0058] However, in the active material layer of the electrode of the present invention, SPAN and lithium titanium oxide need to be selected so that the average secondary particle size of SPAN is larger than the average secondary particle size of lithium titanium oxide. If the average secondary particle size of SPAN is less than the average secondary particle size of lithium titanium oxide, high-speed charging and discharging becomes difficult.
[0059] The average secondary particle size of the lithium titanium oxide can be adjusted by, for example, pulverizing using a pulverizer such as a ball mill or a jet mill, granulating, or classifying by sieving or the like.
[0060] The average secondary particle size (D50) of lithium titanium oxide is the 50% particle size measured by laser diffraction light scattering method, in which the particle size is a volume-based diameter. When the average secondary particle size of lithium titanium oxide is measured by laser diffraction light scattering method, the lithium titanium oxide is dispersed in a dispersion medium such as water or alcohol for measurement.
[0061] The specific surface area of lithium titanium oxide is preferably 1 m 2 / g~200m 2 / g, more preferably 3 m 2 / g~50m 2 / g range. When the specific surface area of lithium titanium oxide is less than 1m 2 / g, the lithium ion absorption into the active material layer may become insufficient. On the other hand, if the specific surface area of lithium titanium oxide exceeds 200m 2 / g, the distribution of the nonaqueous electrolyte may be uneven, which may adversely affect the output characteristics and cycle characteristics of the lithium ion secondary battery.
[0062] In the electrode of the present invention, if at least a portion of the surface of the lithium titanium oxide is coated with a carbon material, the electrode resistance can be reduced, so the lithium titanium oxide can be coated with a carbon material. As a method for producing lithium titanium oxide coated with a carbon material, for example, a method of mixing lithium titanium oxide, a precursor of a carbon material, and a dispersion medium such as water, and calcining the mixture under an inert atmosphere at 500° C. or above can be cited.
[0063] In the active material layer containing SPAN and lithium titanium oxide, the content of lithium titanium oxide is in the range of 5 mass % to 85 mass %, preferably in the range of 10 mass % to 80 mass %. When the content of lithium titanium oxide is less than 5 mass %, the rate characteristics of the lithium ion secondary battery are greatly reduced. On the other hand, when the content of lithium titanium oxide exceeds 85 mass %, the discharge capacity of the lithium ion secondary battery during high-speed charging is reduced.
[0064] It should be noted that a lithium ion secondary battery in which the nonaqueous electrolyte containing a lithium salt is a liquid nonaqueous electrolyte or a polymer gel nonaqueous electrolyte is a liquid battery. The active material layer in the electrode of a liquid battery refers to an electrode mixture layer obtained by volatilizing volatile components such as solvents from a coating formed by applying an electrode mixture paste containing an active material, a binder, and a conductive auxiliary agent on a current collector.
[0065] A lithium ion secondary battery in which the nonaqueous electrolyte containing a lithium salt is a polymer nonaqueous electrolyte, a complex hydride solid electrolyte or an inorganic solid electrolyte is a solid battery. The active material layer in the electrode of a solid battery sometimes contains these nonaqueous electrolytes. It should be noted that in the present invention, a solid battery includes a fully solid battery and a semi-solid battery.
[0066] From the viewpoint of fully exerting battery performance, the total amount of SPAN and lithium titanium oxide contained in the active material layer in the electrode of the liquid battery is preferably 55 mass % or more, more preferably 70 mass % or more, based on the active material layer.
[0067] From the viewpoint of fully exerting battery performance, the total amount of SPAN and lithium titanium oxide contained in the active material layer in the electrode of the solid battery is preferably 40 mass % or more, more preferably 70 mass % or more, based on the active material layer.
[0068] <Electrode Manufacturing Method>
[0069] The electrode of the present invention can be manufactured by a known method. For example, an active material including SPAN and lithium titanium oxide, a complex including a binder and a conductive additive is slurried with an organic solvent or water to produce an electrode mixture paste, and the electrode mixture paste is applied to a collector and dried, thereby manufacturing an electrode having an active material layer formed on the collector.
[0070] As the above-mentioned adhesive, it is not particularly limited, and known adhesives can be used. As the specific example of the adhesive, for example, styrene-butadiene rubber, butadiene rubber, acrylonitrile-butadiene rubber, ethylene-propylene-diene rubber, styrene-isoprene rubber, fluororubber, polyethylene, polypropylene, polyacrylamide, polyamide, polyamide-imide, polyimide, polyacrylonitrile, polyurethane, polyvinylidene fluoride, polytetrafluoroethylene, styrene-acrylate copolymer, ethylene-vinyl alcohol copolymer, polymethyl methacrylate, polyacrylate, polyvinyl alcohol, polyethylene oxide, polyvinyl pyrrolidone, polyvinyl ether, polyvinyl chloride, acrylic acid, polyacrylic acid, methylcellulose, carboxymethyl cellulose, sodium carboxymethyl cellulose, cellulose nanofiber, starch etc. can be listed. The adhesive can be used only one kind, or two or more kinds can be used in combination.
[0071] The content of the binder is preferably 0.5 to 30 parts by mass based on 100 parts by mass of the active material including SPAN and lithium titanium oxide, and more preferably 1 to 20 parts by mass from the viewpoint of good stability of the working electrode.
[0072] The conductive aid may be a conductive aid known as a conductive aid for an electrode. Specific examples of the conductive aid include natural graphite, artificial graphite, coal tar pitch, carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, drum black, disk black, carbon nanotubes, vapor grown carbon fiber (VGCF), exfoliated graphite, graphene, fullerene, needle coke and other carbon materials; metal powders such as aluminum powder, nickel powder, and titanium powder; conductive metal oxides such as zinc oxide and titanium oxide; sulfides such as La2S3, Sm2S3, Ce2S3, and TiS2.
[0073] The average primary particle size of the conductive auxiliary agent is preferably 0.0001 μm to 100 μm, more preferably 0.001 μm to 50 μm.
[0074] The content of the conductive aid is usually 0.1 to 50 parts by mass, preferably 0.5 to 30 parts by mass, and more preferably 1 to 20 parts by mass, based on 100 parts by mass of the active material including SPAN and lithium titanium oxide.
[0075] Examples of the organic solvent include propylene carbonate, ethylene carbonate, diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, 1,2-dimethoxyethane, 1,2-diethoxyethane, acetonitrile, propionitrile, tetrahydrofuran, 2-methyltetrahydrofuran, dioxane, 1,3-dioxolane, nitromethane, N-methylpyrrolidone, N,N-dimethylformamide, dimethylacetamide, methyl ethyl ketone, cyclohexanone, methyl acetate, methyl acrylate, diethyltriamine, N,N-dimethylaminopropylamine, polyethylene oxide, tetrahydrofuran, dimethyl sulfoxide, sulfolane, γ-butyrolactone, and alcohols. The amount of organic solvent or water used can be adjusted according to the coating method selected when applying the electrode mixture paste. For example, when coating is performed using a doctor blade method, it is preferably 10 to 300 parts by mass, and more preferably 20 to 200 parts by mass, relative to 100 parts by mass of the total amount of the active material, binder and conductive aid.
[0076] In the manufacture of electrode mixture paste, within the scope of not damaging the effect of the present invention, for example, electrode mixture paste may also contain other components such as viscosity modifier, reinforcing material, antioxidant, pH modifier, dispersant. As these other components, known materials can be used with known mixing ratios.
[0077] In the manufacture of the electrode mixture paste, when SPAN and lithium titanium oxide, a binder and a conductive aid as active materials are dispersed or dissolved in an organic solvent or water, all the materials can be added to the organic solvent or water at once for dispersion treatment, or they can be added separately for dispersion treatment. When a binder, a conductive aid, and an active material are sequentially added to an organic solvent or water and dispersed, they can be uniformly dispersed in the solvent, so it is preferred. In the case where the electrode mixture paste contains other components, the other components can be added at once for dispersion treatment, but it is preferred to add one other component each time for dispersion treatment.
[0078] There is no particular limitation on the method for the dispersion treatment. As an industrial method, for example, a conventional ball mill, sand mill, bead mill, cyclone mill, Zero mill, pigment disperser, crusher, ultrasonic disperser, homogenizer, Disper disperser, rotation / revolution mixer, planetary mixer, Filmix disperser, jet disperser, etc. can be used.
[0079] As the current collector, conductive materials such as titanium, titanium alloy, aluminum, aluminum alloy, copper, nickel, stainless steel, nickel-plated steel, carbon, conductive resin, etc. can be cited. As the shape of the current collector, foil, plate, mesh, three-dimensional mesh, foam, non-woven fabric, etc. can be cited. The current collector can be any of porous or non-porous. In addition, in order to improve the adhesion and electrical properties, these conductive materials can also be surface treated. Among these conductive materials, aluminum is preferred, and aluminum foil is particularly preferred from the viewpoint of conductivity and price. There is no particular restriction on the thickness of the current collector, and it is usually 5μm to 30μm in the case of foil.
[0080] The method of applying the electrode mixture paste to the collector is not particularly limited, and for example, a die coater method, a notched wheel coater method, a curtain coater method, a spray coater method, a gravure coater method, a flexographic coater method, a knife coater method, a scraper method, a reverse roll method, a brush coating method, an immersion method, etc. can be used. According to the viscosity and dryness of the electrode mixture paste, in terms of the surface state of a good coating film, a die coater method, a knife coater method, a scraper method, and a notched wheel coater method are preferred.
[0081] The electrode mixture paste can be applied to the collector on one side or on both sides. When applied on both sides of the collector, it can be applied on one side successively or on both sides simultaneously. In addition, it can be applied continuously to the surface of the collector, it can be applied intermittently, or it can be applied in strips. The thickness, length and width of the coating can be appropriately determined according to the size of the battery, etc.
[0082] There is no particular limitation on the method for drying the coating of the electrode mixture paste applied on the collector, and a known method can be used. As a drying method, for example, drying by warm air, hot air, low-humidity air, vacuum drying, standing in a heating furnace, etc., and drying by irradiation with far infrared rays, infrared rays or electron beams can be listed. These drying methods can be implemented in combination. The temperature during heating is generally about 50°C to 180°C, and the temperature and other conditions can be appropriately set according to the coating amount of the electrode mixture paste, the boiling point of the solvent used, the type of adhesive, etc. By this drying, volatile components such as the solvent evaporate from the coating of the electrode mixture paste, and an electrode mixture layer is formed on the collector.
[0083] SPAN is a material that does not contain lithium originally. Since it has irreversible capacity, it can be pre-doped with lithium. As methods for doping SPAN with lithium, for example, there are: a method of inserting lithium by electrolytic doping in which a half-cell is assembled using metallic lithium in the counter electrode and lithium is electrochemically doped; a method of inserting lithium by attachment doping in which a metallic lithium foil is attached to an electrode and then placed in an electrolyte and lithium is doped by diffusion into the electrode; a mechanical doping method in which lithium is inserted by mechanically colliding the active material layer containing SPAN with lithium metal; a chemical doping method in which lithium is inserted by immersing the electrode in a lithium naphthalene solution, etc., but the present invention is not limited to these methods.
[0084] Next, the lithium ion secondary battery of the present invention is described. The lithium ion secondary battery of the present invention is characterized in that it comprises a positive electrode, a negative electrode, and a non-aqueous electrolyte containing a lithium salt, and the positive electrode or the negative electrode uses the above-mentioned electrode.
[0085] <Method for producing counter electrode>
[0086] In the lithium ion secondary battery of the present invention, examples of the counter electrode to the electrode of the present invention include metallic lithium, or an electrode containing a lithium-containing composite oxide, silicon, silicon oxide, graphite, carbon, or the like as an active material.
[0087] When metallic lithium is used as the counter electrode, the counter electrode may be composed of metallic lithium and / or a lithium alloy. Alternatively, the counter electrode may include a current collector composed of a conductive material of metallic lithium and / or a lithium alloy. In this case, an active material layer containing lithium metal may be formed. The active material layer may be formed, for example, by attaching a foil-shaped metallic lithium, or by electro-deposition or evaporation of metallic lithium.
[0088] The above-mentioned composite oxide containing lithium is selected from the group consisting of lithium transition metal composite oxide, lithium transition metal silicate compound, and lithium transition metal sulfate compound. The transition metal contained in these compounds is not particularly limited, and from the good charge and discharge stability of lithium ion secondary battery, preferably aluminum, titanium, vanadium, chromium, manganese, iron, cobalt, nickel, copper, zinc, magnesium, gallium, zirconium, niobium, boron, calcium, molybdenum and tungsten, aluminum, vanadium, titanium, chromium, manganese, iron, cobalt, nickel and copper become significant due to the effect of the present invention, so it is preferred, aluminum, manganese, iron, cobalt and nickel become more significant due to the effect of the present invention, so it is preferred.
[0089] Examples of the lithium transition metal composite oxide include LiCoO 2 , LiNiO 2 , LiMnO 2 , a compound represented by the following general formula (2), and a compound represented by the following general formula (3).
[0090] Li g Ni h Co i M1 j O2(2)
[0091] Li (1+x) Mn (2-x-y) M1 y O4(3)
[0092] In the formula, g, h, i and j satisfy 0.9≤g≤1.2, 0.3<h<1, 0≤i≤0.5, 0≤j≤0.5, h+i+j=1, x satisfies 0≤x<0.5, and y satisfies 0≤y<0.5. M1 is preferably at least one selected from aluminum, titanium, vanadium, chromium, manganese, iron, copper, zinc, magnesium, gallium, zirconium, niobium, boron, calcium, molybdenum and tungsten.
[0093] Specific examples of the compound represented by the general formula (2) or the compound represented by the general formula (3) include LiMn2O4, LiNi 0.5 Co 0.2 Mn 0.3 O2、LiNi 0.8 Co 0.1 Mn 0.1 O2、LiNi 0.5 Mn 1.5 O4、LiNi 0.80 Co 0.15 Al 0.05 O2、LiNi 0.80 Co 0.17 Al 0.03 O2、LiNi 0.90 Co 0.05 Al 0.05 O2、LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2、LiNi 0.6 Co 0.2 Mn 0.2 O2、LiNi 0.9 Co 0.05 Mn 0.05 O2、LiMn 1.8 Al 0.2 O4、Li 1.1 Mn 1.8 Mg 0.1 O4、Li 1.1 Mn 1.85 Al 0.05 O4, Li2MnO3-LiMO2 (M = cobalt, nickel, manganese), etc.
[0094] As the lithium transition metal composite oxide, LiCoO2, LiMn2O4, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3O2、LiNi 0.5 Co 0.2 Mn 0.3 O2、LiNi 0.6 Co 0.2 Mn 0.2 O2、LiNi 0.8 Co 0.1 Mn 0.1 O2、LiNi 0.8 Co 0.15 Al 0.05 O2.
[0095] Examples of the lithium transition metal phosphate compound include compounds represented by the following general formula (4).
[0096] Li k M2 m (PO4) n F p (4)
[0097] In the formula, k is 0<k≤3, m is 0.5≤m≤2, n is 1≤n≤3, and p is 0≤p≤1. M2 is at least one selected from the group consisting of iron, cobalt, nickel, manganese, copper, titanium, tungsten, molybdenum, chromium, vanadium and vanadium monoxide (II). From the perspective of good charge and discharge stability, at least one selected from the group consisting of iron, cobalt, nickel, manganese, copper, vanadium and vanadium monoxide (II). In addition, a part of M2 can be replaced by one or more other metals such as aluminum, zinc, magnesium, zirconium, gallium, and niobium.
[0098] Specific examples of the lithium transition metal phosphate compounds include LiFePO4, LiMn X Fe 1-X PO4, LiCuPO4, LiNiPO4, LiCoPO4, LiMnPO4, LiVOPO4, Li2FePO4, Li2NiPO4, Li2CoPO4, Li2MnPO4, Li2NiPO4F, Li2CoPO4F, Li2MnPO4F, Li2FePO4F, Li3V2(PO4)3, LiMn 7 / 8 Fe 1 / 8 PO4、LiMn 2 / 3 Fe 1 / 3 PO4、LiFe 0.9 Mn 0.1 PO4、LiFe 0.2 Mn 0.8 PO4、LiFe 0.15 Mn 0.75 Mg 0.1 PO4、LiFe 0.19 Mn 0.75 Zr0.03 PO4, etc.
[0099] As the above-mentioned lithium transition metal phosphate compound, LiFePO4, LiCuPO4, LiNiPO4, LiCoPO4, LiMnPO4, and LiVOPO4 are preferred in view of good charge and discharge stability, and LiFePO4, LiNiPO4, LiCoPO4, and LiMnPO4 are more preferred.
[0100] The active material of the counter electrode is preferably pulverized, granulated, or the like to obtain a desired particle size, and more preferably classified. The pulverization and classification methods may be the same as those described in the pulverization and classification methods of SPAN.
[0101] The average secondary particle size (D50) of the active material of the electrode is preferably 0.1 μm to 50 μm, more preferably 0.5 μm to 50 μm, and further preferably 1 μm to 30 μm. If the average secondary particle size of the active material of the electrode exceeds 50 μm, it is sometimes impossible to uniformly form a smooth active material layer. On the other hand, if the average secondary particle size of the active material of the electrode is less than 0.1 μm, it is easy to deteriorate the handling (operability) and the side reactions caused by the increase in specific surface area, which sometimes have an adverse effect on the charge and discharge stability.
[0102] The counter electrode can be manufactured by a known method. The counter electrode having an active material layer formed on the current collector can be manufactured by slurrying a complex containing the counter electrode active material, a binder and a conductive auxiliary agent with an organic solvent or water, applying the electrode mixture paste to a current collector and drying it.
[0103] Examples of the binder used in the counter electrode include the same binders as those described above, and polyvinylidene fluoride, polyimide, polyacrylonitrile, polytetrafluoroethylene, polyacrylic acid, and sodium carboxymethylcellulose are preferred because of good charge and discharge stability.
[0104] The content of the binder is preferably 0.5 to 30 parts by mass, more preferably 1 to 20 parts by mass, based on 100 parts by mass of the active material of the counter electrode.
[0105] Examples of the conductive aid used in the counter electrode include the same conductive aids as those described above.
[0106] The content of the conductive auxiliary agent is preferably 0.1 to 50 parts by mass, more preferably 0.5 to 30 parts by mass, and even more preferably 1 to 20 parts by mass, based on 100 parts by mass of the active material of the counter electrode.
[0107] As a solvent for preparing the electrode mixture paste of the counter electrode, the same solvent as the solvent for preparing the above-mentioned electrode mixture paste can be used. The amount of the solvent used can be adjusted according to the coating method selected when applying the electrode mixture paste, for example, when applying by a doctor blade method, relative to 100 parts by mass of the total amount of the active material, binder and conductive auxiliary agent of the counter electrode, preferably 10 parts by mass to 300 parts by mass, more preferably 20 parts by mass to 200 parts by mass.
[0108] In the electrode mixture paste of the electrode, in the scope that does not damage the effect of the present invention, in addition to the above-mentioned components, other components such as viscosity modifier, reinforcing material, antioxidant, pH adjusting agent, dispersant can also be contained. As these other components, known materials can be used with known mixing ratio.
[0109] In the manufacture of the electrode mixture paste for the electrode, when the active material, binder and conductive aid of the electrode are dispersed or dissolved in an organic solvent or water, all the materials can be added to the solvent at once for dispersion treatment, or they can be added separately for dispersion treatment. When the binder, conductive aid and active material of the electrode are added to the organic solvent or water in sequence and dispersed, they can be evenly dispersed in the solvent, so it is preferred. In the case where the electrode mixture paste for the electrode contains other components, the other components can be added at once for dispersion treatment, but it is preferred to add one other component at a time for dispersion treatment.
[0110] Examples of the dispersion treatment method and current collector in the production of the electrode mixture paste for the counter electrode include the same dispersion treatment method and current collector as those described in the production of the electrode mixture paste.
[0111] The method of applying the electrode mixture paste of the counter electrode to the current collector and the method of drying the electrode mixture paste of the counter electrode can be used in the same manner as the method described as the method of applying the electrode mixture paste to the current collector and the method of drying the electrode mixture paste.
[0112] <Method for producing lithium-ion secondary battery>
[0113] The lithium ion secondary battery of the present invention can be manufactured by a known method for manufacturing a lithium ion secondary battery, except that an electrode containing SPAN and lithium titanium oxide is used as a working electrode. For example, a separator can be sandwiched between the working electrode and the counter electrode and held in a battery cell, and a non-aqueous electrolyte is introduced into the battery cell, followed by sealing and sealing. The following describes the various materials of the lithium ion secondary battery.
[0114] <Non-aqueous electrolyte>
[0115] The non-aqueous electrolytes that can be used in the lithium-ion secondary battery of the present invention include: a liquid non-aqueous electrolyte obtained by dissolving a lithium salt in an organic solvent; a polymer gel non-aqueous electrolyte obtained by dissolving or dispersing a lithium salt using a polymer gel that is gelled by dissolving a polymer compound in an organic solvent as a solvent or dispersion medium; a polymer non-aqueous electrolyte obtained by dispersing a lithium salt using a polymer as a dispersion medium without using a solvent (in this specification, an electrolyte obtained by dispersing a lithium salt using a polymer as a dispersion medium without using a solvent is defined as a polymer electrolyte); a complex hydride solid electrolyte; an inorganic solid electrolyte, etc.
[0116] <Lithium salt>
[0117] As the lithium salt used in the non-aqueous electrolyte, there is no particular limitation, and known lithium salts that can be used as lithium salts of lithium ion secondary batteries can be used. As specific examples of lithium salts, for example, LiPF6, LiBF4, LiAsF6, LiCF3SO3, LiCF3CO2, LiN(CF3SO2)2, LiN(C2F5SO2)2, LiN(SO2F)2, LiC(CF3SO2)3, LiB(CF3SO3)4, LiB(C2O4)2, LiBF2(C2O4), LiSbF6, LiSiF5, LiSCN, LiClO4, LiCl, LiF, LiBr, LiI, LiAlF4, LiAlCl4, LiPO2F2, their derivatives, etc. can be cited.
[0118] As lithium salts used in liquid electrolytes and polymer gel electrolytes, it is preferred to use one or more selected from the group consisting of LiPF6, LiBF4, LiClO4, LiCF3SO3, LiN(CF3SO2)2, LiN(C2F5SO2)2, LiN(SO2F)2, LiPO2F2, LiC(CF3SO2)3, and derivatives of LiCF3SO3 and derivatives of LiC(CF3SO2)3.
[0119] As the lithium salt used in the polymer electrolyte (or the polymer electrolyte obtained by dispersing the lithium salt without using a solvent), it is preferred to use one or more selected from the group consisting of LiPF6, LiBF4, LiClO4, LiN(CF3SO2)2, LiN(C2F5SO2)2, LiN(SO2F)2, LiC(CF3SO2)3, LiB(CF3SO3)4, and LiB(C2O4)2.
[0120] If the concentration of the lithium salt in the non-aqueous electrolyte is too low, sufficient current density may not be obtained. On the other hand, if it is too high, the stability of the non-aqueous electrolyte may be impaired. Therefore, the concentration of the lithium salt is preferably 0.5 mol / L to 7 mol / L, and more preferably 0.8 mol / L to 1.8 mol / L.
[0121] <Liquid non-aqueous electrolyte>
[0122] When a liquid nonaqueous electrolyte is used as the nonaqueous electrolyte, it is preferred that the liquid nonaqueous electrolyte contain at least one compound selected from cyclic carbonate compounds.
[0123] As the cyclic carbonate compound, for example, saturated cyclic carbonate compounds such as ethylene carbonate, 1,2-propylene carbonate, 1,3-propylene carbonate, 1,2-butylene carbonate, 1,3-butylene carbonate, 1,1-dimethylethylene carbonate, and unsaturated cyclic carbonate compounds such as vinylene carbonate, vinyl ethylene carbonate, propylene carbonate (propylidene carbonate), ethylene ethylidene carbonate (ethylene ethylidene carbonate), and ethylene isopropylidene carbonate (ethylene isopropylidene carbonate) can be cited. A part of the hydrogen atoms of these cyclic carbonate compounds can be substituted by fluorine atoms.
[0124] In the case of containing cyclic carbonate compounds as non-aqueous electrolytes, from the viewpoint that viscosity decreases and ion conductivity improves, it is preferred to further contain chain carbonate compounds. As chain carbonate compounds, for example, saturated chain carbonate compounds such as dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, and dipropyl carbonate can be cited; unsaturated chain carbonate compounds such as dipropargyl carbonate, propargyl methyl carbonate, ethyl carbonate propargyl ester, carbonate bis (1-methyl propargyl) ester, and carbonate bis (1-dimethyl propargyl) ester. A part of the hydrogen atoms of these chain carbonate compounds can be replaced by fluorine atoms.
[0125] From the perspective of the performance and storage stability of the lithium ion secondary battery, the liquid nonaqueous electrolyte is preferably propylene carbonate, a mixed solvent of ethylene carbonate and dimethyl carbonate, a mixed solvent of ethylene carbonate and ethyl methyl carbonate, a mixed solvent of ethylene carbonate and diethyl carbonate, a mixed solvent of propylene carbonate and dimethyl carbonate, a mixed solvent of propylene carbonate and diethyl carbonate, a mixed solvent of propylene carbonate, ethylene carbonate and ethyl methyl carbonate, and more preferably propylene carbonate, a mixed solvent of ethylene carbonate and ethyl methyl carbonate, a mixed solvent of ethylene carbonate and diethyl carbonate, a mixed solvent of propylene carbonate and diethyl carbonate, and a mixed solvent of propylene carbonate, ethylene carbonate and ethyl methyl carbonate.
[0126] In the case where the liquid nonaqueous electrolyte also comprises a chain carbonate compound, the mixing ratio of the cyclic carbonate compound and the chain carbonate compound is preferably relative to 100 parts by volume of the cyclic carbonate compound, and the chain carbonate compound is 10 parts by volume~1000 parts by volume. When the chain carbonate compound is less than 10 parts by volume, the performance of the lithium ion secondary battery sometimes decreases. On the other hand, when the chain carbonate compound exceeds 1000 parts by volume, the charge and discharge stability under the high temperature of the lithium ion secondary battery sometimes decreases.
[0127] The liquid nonaqueous electrolyte may contain an organic solvent commonly used in the nonaqueous electrolyte of a lithium ion secondary battery. As a specific example of the organic solvent, for example, saturated cyclic ester compounds, sulfoxide compounds, sulfone compounds, amide compounds, chain ether compounds, cyclic ether compounds, saturated chain ester compounds, etc. may be listed. These organic solvents may be added with only one or more of two or more.
[0128] Examples of the saturated cyclic ester compound include γ-butyrolactone, γ-valerolactone, γ-caprolactone, δ-caprolactone, and δ-octanolactone.
[0129] Examples of the sulfoxide compound include dimethyl sulfoxide, diethyl sulfoxide, dipropyl sulfoxide, diphenyl sulfoxide, and thiophene.
[0130] Examples of the sulfone compound include dimethyl sulfone, diethyl sulfone, dipropyl sulfone, diphenyl sulfone, sulfolane (also called tetramethylene sulfone), 3-methylsulfolane, 3,4-dimethylsulfolane, 3,4-diphenylmethylsulfolane, sulfolene, 3-methylsulfolene, 3-ethylsulfolene, 3-bromomethylsulfolene, etc. Among them, sulfolane and tetramethylsulfolane are preferred.
[0131] Examples of the amide compound include N-methylpyrrolidone, dimethylformamide, and dimethylacetamide.
[0132] Examples of the chain ether compound and the cyclic ether compound include dimethoxyethane, ethoxymethoxyethane, diethoxyethane, tetrahydrofuran, dioxolane, dioxane, 1,2-bis(methoxycarbonyloxy)ethane, 1,2-bis(ethoxycarbonyloxy)ethane, 1,2-bis(ethoxycarbonyloxy)propane, ethylene glycol bis(trifluoroethyl) ether, propylene glycol bis(trifluoroethyl) ether, ethylene glycol bis(trifluoromethyl) ether, and diethylene glycol bis(trifluoroethyl) ether. Among them, dioxolane is preferred.
[0133] As the saturated chain ester compound, a monoester compound and a diester compound having a total of 2 to 8 carbon atoms in the molecule are preferred. Specific examples of the compound include methyl formate, ethyl formate, methyl acetate, ethyl acetate, propyl acetate, isobutyl acetate, butyl acetate, methyl propionate, ethyl propionate, methyl butyrate, methyl isobutyrate, trimethyl methyl acetate, trimethyl ethyl acetate, methyl malonate, ethyl malonate, methyl succinate, ethyl succinate, methyl 3-methoxypropionate, ethyl 3-methoxypropionate, ethylene glycol diacetate, propylene glycol diacetate, and the like. Methyl formate, ethyl formate, methyl acetate, ethyl acetate, propyl acetate, isobutyl acetate, butyl acetate, methyl propionate, and ethyl propionate are preferred.
[0134] As other organic solvents, for example, acetonitrile, propionitrile, nitromethane, derivatives thereof, and various ionic liquids can also be used.
[0135] <Polymer gel non-aqueous electrolyte>
[0136] Examples of polymers that can be used as polymer gels include polyethylene oxide, polypropylene oxide, polyvinyl chloride, polyacrylonitrile, polymethyl methacrylate, polyethylene, polyvinylidene fluoride, polyhexafluoropropylene, polystyrene sulfonic acid, etc. There are no particular restrictions on the organic solvent used to dissolve the polymer to form a gel, the mixing ratio of the lithium salt to the polymer gel, and the method for producing the polymer gel, and any organic solvent, lithium salt, or production method known in the art can be used.
[0137] <Polymer nonaqueous electrolyte>
[0138] Examples of polymers that can be used as a polymer nonaqueous electrolyte obtained by dispersing a lithium salt using a polymer as a dispersion medium without using a solvent include polyethylene oxide, polypropylene oxide, and polystyrene sulfonic acid.
[0139] There are no particular limitations on the mixing ratio of the lithium salt and the polymer in the polymer nonaqueous electrolyte and the method for producing the polymer nonaqueous electrolyte, and mixing ratios and production methods known in the technical field can be used.
[0140] <Complex Hydride-based Solid Electrolyte>
[0141] Examples of complex hydride solid electrolytes include Li(CB9H 10 )、Li(CB 11 H 12 )、Li2(B 12 H 12), Li(BH4), 3(LiBH4)-LiI, Li(NH2), Li(AlH4), Li3(AlH6), 3(LiBH4)-Li(NH2), Li(BH4)-Li(NH2), 0.7Li(CB9H 10 )-0.3Li(CB 11 H 12 ), Li(BH4)-3KI, Li(BH4)-P2I4, Li(BH4)-P2S5, Li2(NH2), Li(BH4)-GdCl3, Li(BH4)-NaI, Li(BH4)-3Li(NH2), etc.
[0142] <Inorganic solid electrolyte>
[0143] Examples of the inorganic solid electrolyte include sulfide solid electrolytes, oxide solid electrolytes, and phosphoric acid solid electrolytes.
[0144] As sulfide-based solid electrolytes, there are Li2S-P2S5 compounds, Li2S-SiS2 compounds, Li2S-GeS2 compounds, Li2S-B2S3 compounds, Li2S-P2S3 compounds, LiI-Si2S-P2S5, LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, Li 10 GeP2S 12 Etc. It should be noted that in this specification, the term "system compound" is used as a general term for solid electrolytes that mainly contain raw materials such as "Li2S" and "P2S5" recorded before the "system compound". For example, the Li2S-P2S5 system compound includes a solid electrolyte that mainly contains Li2S and P2S5 and may further contain other raw materials. In addition, the Li2S-P2S5 system compound also includes solid electrolytes with different mixing ratios of Li2S and P2S5.
[0145] Examples of Li2S-P2S5 compounds include Li2S-P2S5, Li2S-P2S5-LiI, Li2S-P2S5-LiCl, Li2S-P2S5-LiBr, Li2S-P2S5-Li2O, Li2S-P2S5-Li2O-LiI, Li2S-P2S5-Z m S n (Z is Ge, Zn or Ga, m and n are positive numbers), etc.
[0146] Examples of Li2S-SiS2 compounds include Li2S-SiS2, Li2S-SiS2-LiI, Li2S-SiS2-LiBr, Li2S-SiS2-LiCl, Li2S-SiS2-B2S3-LiI, Li2S-SiS2-P2S5-LiI, Li2S-SiS2-Li3PO4, Li2S-SiS2-Li2SO4, Li2S-SiS2-Li x MO y (M is P, Si, Ge, B, Al, Ga or In, x and y are positive numbers), etc.
[0147] Examples of Li2S-GeS2 compounds include Li2S-GeS2, Li2S-GeS2-P2S5, and the like.
[0148] Examples of the oxide-based solid electrolyte include perovskite-type oxides, Nasicon-type oxides, Lisicon-type oxides, garnet-type oxides, and β-alumina oxides.
[0149] Examples of perovskite-type oxides include Li a La 1-a Li-La-Ti perovskite oxides such as Li b La 1-b Li-La-Ta perovskite oxides such as Li c La 1-c Li-La-Nb-based perovskite-type oxides represented by NbO3, etc. (0<a<1, 0<b<1, 0<c<1).
[0150] Examples of Nasicon-type oxides include Li d+l Al d Ti 2-d Li crystals represented by (PO4)3 are the main crystals e X f Y g P h O j (X is B, Al, Ga, In, C, Si, Ge, Sn, Sb or Se, Y is Ti, Zr, Ge, In, Ga, Sn or Al, 0≤d≤1, e, f, g, h and j are positive numbers) etc. As a specific example of Nasicon type oxide, LiTi2(PO4)3 can be cited.
[0151] Examples of Lisicon-type oxides include oxides represented by Li4XO4-Li3YO4 (X is Si, Ge or Ti, and Y is P, As or V).
[0152] As garnet-type oxides, for example, Li7La3Zr2O 12 Li-La-Zr series oxides and their derivatives represented by etc.
[0153] In the lithium ion secondary battery of the present invention, the form of the nonaqueous electrolyte is not particularly limited, but a liquid nonaqueous electrolyte is preferably used from the viewpoint of simplicity of the production process.
[0154] In order to improve battery life, improve safety, etc., the non-aqueous electrolyte may further contain known electrolyte additives such as electrode film forming agents, antioxidants, flame retardants, and overcharge preventers. The concentration when using electrolyte additives is preferably 0.01% by mass to 10% by mass, and more preferably 0.1% by mass to 5% by mass relative to the non-aqueous electrolyte. If less than 0.01% by mass, sometimes the addition effect cannot be exerted, and if more than 10% by mass, sometimes the characteristics of the lithium ion secondary battery are adversely affected.
[0155] <Separator>
[0156] In the lithium ion secondary battery of the present invention, when a liquid nonaqueous electrolyte is used as the nonaqueous electrolyte, it is preferred that the separator is between the working electrode and the counter electrode. The separator can be selected without particular limitation to use the polymer film, nonwoven fabric and glass filter commonly used in lithium ion secondary batteries. As a specific example of a polymer film, for example, a polymer compound based on polyethers such as polyethylene, polypropylene, polyvinylidene fluoride, polyvinylidene chloride, polyacrylonitrile, polyacrylamide, polytetrafluoroethylene, polysulfone, polyether sulfone, polycarbonate, polyamide, polyimide, polyethylene oxide and polypropylene oxide, various celluloses such as carboxymethyl cellulose and hydroxypropyl cellulose, poly (meth) acrylic acid and its various esters, etc., its derivatives, their copolymers, and mixtures thereof can be cited, and these polymer films can also be coated with ceramic materials such as aluminum oxide or silicon dioxide, magnesium oxide, aromatic polyamide resin, and polyvinylidene fluoride. These polymer films can be used alone, or these films can be overlapped and used as multilayer films. Furthermore, various additives may be used in these polymer membranes, and there are no particular restrictions on the type and content of additives. Among these polymer membranes, it is preferred to use a membrane selected from polyethylene, polypropylene, polyvinylidene fluoride, and polysulfone.
[0157] For these polymer membranes, a polymer membrane that has been microporous in a manner that allows non-aqueous electrolytes to penetrate so that ions can easily pass through is used. As a method for microporousization, there can be cited a "phase separation method" in which a polymer compound and a solvent solution are microphase-separated while forming a membrane, and the solvent is extracted to remove the membrane to make it porous; a "stretching method" in which a molten polymer compound is extruded at a high draw and then heat-treated to arrange crystals in one direction, and then a gap is formed between the crystals by stretching to achieve porosity, etc., and the method can be appropriately selected according to the polymer membrane used.
[0158] When a polymer gel electrolyte, a polymer electrolyte (or a polymer electrolyte obtained by dispersing a lithium salt without using a solvent), a complex hydride solid electrolyte, or an inorganic solid electrolyte is used as the nonaqueous electrolyte, a separator may not be included.
[0159] <External packaging>
[0160] The shape of the lithium ion of the present invention is not particularly limited, and can be a battery of various shapes such as a coin-shaped battery, a cylindrical battery, a square battery, a laminated battery, etc., and a metal container or a laminated film can be used as an external packaging member. The thickness of the external packaging member is usually less than 0.5mm, preferably less than 0.3mm. As the shape of the external packaging member, flat (thin), square, cylindrical, coin-shaped, button-shaped, etc. can be cited.
[0161] Examples of metal containers include containers made of stainless steel, aluminum, or aluminum alloys. The aluminum alloy is preferably an alloy containing elements such as magnesium, zinc, and silicon. By setting the content of transition metals such as iron, copper, nickel, and chromium in aluminum or aluminum alloys to 1% or less, long-term reliability and heat dissipation in high-temperature environments can be dramatically improved.
[0162] The laminated film can be a multilayer film having a metal layer between resin films. For light weight, the metal layer is preferably aluminum foil or aluminum alloy foil. The resin film can be made of a polymer material such as polypropylene, polyethylene, nylon, polyethylene terephthalate, etc. The laminated film can be sealed by heat fusion to form an exterior component.
[0163] Figure 1 An example of a coin-type battery of the lithium ion secondary battery of the present invention is shown. Figure 2 and Figure 3 An example of a cylindrical battery is shown. Figures 4 to 6 An example of a stacked battery is shown.
[0164] exist Figure 1In the coin-type lithium-ion secondary battery 10 shown, 1 is a positive electrode capable of releasing lithium ions, 1a is a positive electrode collector, 2 is a negative electrode capable of absorbing and releasing lithium ions released from the positive electrode, 2a is a negative electrode collector, 3 is a non-aqueous electrolyte, 4 is a positive electrode shell made of stainless steel, 5 is a negative electrode shell made of stainless steel, 6 is a gasket made of polypropylene, and 7 is a separator made of polyethylene.
[0165] exist Figure 2 and Figure 3 In the cylindrical lithium ion secondary battery 10' shown, 11 is a negative electrode, 12 is a negative electrode collector, 13 is a positive electrode, 14 is a positive electrode collector, 15 is a non-aqueous electrolyte, 16 is a separator, 17 is a positive electrode terminal, 18 is a negative electrode terminal, 19 is a negative electrode plate, 20 is a negative electrode lead, 21 is a positive electrode plate, 22 is a positive electrode lead, 23 is a casing, 24 is an insulating plate, 25 is a gasket, 26 is a safety valve, and 27 is a PTC element.
[0166] Figure 4 2 is an exploded perspective view schematically showing an electrode group 29 of a stacked lithium ion secondary battery 28. In the embodiments described below, a stacked lithium ion secondary battery is used for description, but the present invention is not limited thereto. The electrode group 29 has, for example, a structure in which sheet-like negative electrodes 11, sheet-like positive electrodes 13, and sheet-like separators 16 for separating the negative electrodes 11 and the positive electrodes 13 are alternately stacked. 17 is a positive electrode terminal, and 18 is a negative electrode terminal.
[0167] Figure 5 is an exploded perspective view schematically showing a stacked lithium-ion secondary battery 28, Figure 6 1 is a schematic plan view showing the appearance of a laminated lithium ion secondary battery 28. Reference numeral 17 denotes a positive electrode terminal, reference numeral 18 denotes a negative electrode terminal, reference 29 denotes an electrode group, reference 30 denotes a laminated film on the case side, and reference 31 denotes a laminated film on the cover side.
[0168] Although the embodiments of the present invention have been described above, the present invention is not limited to the above embodiments, and can be implemented in various forms that can be modified and improved by those skilled in the art without departing from the gist of the present invention.
[0169] Example
[0170] The present invention will be described in more detail below with reference to Examples and Comparative Examples, but the present invention is not limited to these Examples.
[0171] [Manufacturing Example 1] Manufacture of SPAN
[0172] After a mixture of 200 parts by mass of sulfur (manufactured by Sigma-Aldrich Co., Ltd., particle size 200 μm, powder) and 100 parts by mass of polyacrylonitrile powder (manufactured by Sigma-Aldrich Co., Ltd., classified using a sieve with an opening diameter of 30 μm) was placed in an alumina Tammann tube, the opening of the alumina Tammann tube was plugged with a rubber stopper equipped with a thermocouple, a gas introduction tube and a gas discharge tube. While introducing argon gas into the alumina Tammann tube at a flow rate of 100 cc / min, the mixture was heated at a heating rate of 5°C / min, and the heating was stopped when it reached 360°C, and the temperature was raised to 400°C. After cooling to room temperature under natural air cooling, the reaction product was taken out from the alumina Tammann tube. The obtained reaction product was pulverized after removing the elemental sulfur by heating to obtain SPAN. The average secondary particle size of the obtained SPAN was 9 μm, and the sulfur content was 38% by mass.
[0173] [Manufacturing Example 2] Manufacture of Carbon-Coated LTO
[0174] Lithium titanium oxide (Li4Ti5O 12 ) (manufactured by Ishihara Sangyo Co., Ltd., average particle size: 7 μm), 100 ml of pure water, stirred for 1 hour, and further irradiated with ultrasound for 6 minutes. After cooling the obtained slurry in an ice bath, 3 g of acrylonitrile and 25 mg of 2,2'-azobis(isobutyronitrile) were added, and ultrasound was irradiated for 6 minutes. Then, under nitrogen reflux, the slurry was degassed for 30 minutes, the temperature was raised to 70°C, and heated for 12 hours. The obtained slurry was vacuum dried and allowed to stand at room temperature (25°C).
[0175] In air, the temperature was raised from 25°C to 240°C at a rate of 5°C / min and maintained at 240°C for 1 hour. Further, under nitrogen reflux, the temperature was raised to 700°C at a rate of 5°C / min to produce carbon-coated LTO in which the surface of lithium titanium oxide was coated with carbon. The average particle size of the obtained carbon-coated LTO was 8 μm.
[0176] [Example 1] Preparation of Electrode A
[0177] 45.0 parts by mass of SPAN prepared in Preparation Example 1 and lithium titanium oxide (Li4Ti5O 12) (manufactured by Ishihara Sangyo Co., Ltd., with an average secondary particle size of 7 μm), 45.0 parts by mass of acetylene black (manufactured by Denka Co., Ltd.) as a conductive aid, 5.0 parts by mass of styrene-butadiene rubber (40% by mass aqueous dispersion, manufactured by Nippon Zeon Co., Ltd.) as a binder (solid content), and 2.0 parts by mass of sodium carboxymethyl cellulose (manufactured by Dicelphinc Kem Co., Ltd.) were added to 110 parts by mass of water as a solvent, and they were mixed for 30 minutes at a revolution of 1,600 rpm and a rotation of 640 rpm using a rotation / revolution mixer to prepare an electrode mixture paste.
[0178] The obtained electrode mixture paste was applied to one side of a collector composed of a carbon-coated aluminum foil (thickness 22 μm) by a doctor blade method, and after standing at 80° C. for 1 hour to dry, it was pressed to form an active material layer on the collector. Then, the aluminum foil with the active material layer was cut into a predetermined size (circular), and further vacuum dried at 130° C. for 2 hours just before use to prepare electrode A.
[0179] [Example 2] Preparation of Electrode B
[0180] The electrode active material in Example 1 was replaced with 72 parts by mass of SPAN prepared in Preparation Example 1 and lithium titanium oxide (Li4Ti5O 12 Electrode B was prepared in the same manner as in Example 1 except that 18 parts by mass of ) (manufactured by Ishihara Sangyo Co., Ltd., average secondary particle size 7 μm) was added.
[0181] [Example 3] Production of Electrode C
[0182] The electrode active material in Example 1 was replaced with 18 parts by mass of SPAN prepared in Preparation Example 1 and lithium titanium oxide (Li4Ti5O 12 Electrode C was prepared in the same manner as in Example 1 except that 72 parts by mass of ) (manufactured by Ishihara Sangyo Co., Ltd., average secondary particle size 7 μm) was added.
[0183] [Comparative Example 1] Production of Electrode D
[0184] The electrode active material in Example 1 was replaced with 45 parts by mass of SPAN prepared in Preparation Example 1 and lithium titanium oxide (Li4Ti5O 12 Electrode D was prepared in the same manner as in Example 1 except that 45 parts by mass of ) (manufactured by Ishihara Sangyo Co., Ltd., average secondary particle size: 15 μm) was added.
[0185] [Comparative Example 2] Production of Electrode E
[0186] Electrode E was prepared in the same manner as in Example 1, except that the electrode active material in Example 1 was changed to 90 parts by mass of SPAN produced in Production Example 1.
[0187] [Comparative Example 3] Production of Electrode F
[0188] The electrode active material in Example 1 was changed to only lithium titanium oxide (Li4Ti5O 12 Electrode F was prepared in the same manner as in Example 1 except that 90 parts by mass of ) (manufactured by Ishihara Sangyo Co., Ltd., average secondary particle size 7 μm) was added.
[0189] [Comparative Example 4] Production of Electrode G
[0190] Electrode G was produced in the same manner as in Example 1, except that the electrode active material in Example 1 was changed to 90 parts by mass of the carbon-coated LTO produced in Production Example 2 alone.
[0191] [Comparative Example 5] Production of Electrode H
[0192] The electrode active material in Example 1 was replaced with 8 parts by mass of SPAN 8 and lithium titanium oxide (Li4Ti5O 12 Electrode H was prepared in the same manner as in Example 1 except that 2 parts by mass of ) (manufactured by Ishihara Sangyo Co., Ltd., average secondary particle size 7 μm) was added.
[0193] [Comparative Example 6] Preparation of Electrode I
[0194] The electrode active material in Example 1 was replaced with 2 parts by mass of SPAN prepared in Preparation Example 1 and lithium titanium oxide (Li4Ti5O 12 Electrode I was prepared in the same manner as in Example 1, except that 88 parts by mass of ) (manufactured by Ishihara Sangyo Co., Ltd., average secondary particle size 7 μm) was added.
[0195] [Example 4] Production of Lithium Ion Secondary Battery A
[0196] As the working electrode, electrode A was used, as the counter electrode, lithium metal with a thickness of 500 μm cut in a circle was used, and as the separator, a glass filter was clamped between the working electrode and the counter electrode and maintained in the shell. As a non-aqueous electrolyte, a non-aqueous electrolyte adjusted in a mixed solvent consisting of 30 volume % of ethylene carbonate and 70 volume % of ethyl methyl carbonate so that LiPF6 had a concentration of 1.0 ml / L was sealed in the shell, and the shell was sealed and sealed using a riveting machine to produce a coin-shaped lithium-ion secondary battery A with a diameter of 20 mm and a thickness of 3.2 mm. The capacity of the battery is 3 mAh. A schematic diagram of the coin-shaped lithium-ion secondary battery is shown in Figure 1 .
[0197] [Example 5] Production of lithium ion secondary battery B
[0198] A lithium ion secondary battery B was prepared by the same procedure as in Example 4 except that the electrode A serving as the working electrode was changed to the electrode B. The capacity of the battery was 3 mAh.
[0199] [Example 6] Production of lithium-ion secondary battery C
[0200] A lithium ion secondary battery C was produced by the same procedure as in Example 4 except that the electrode A serving as the working electrode was changed to the electrode C. The capacity of the battery was 3 mAh.
[0201] [Comparative Example 7] Production of Lithium Ion Secondary Battery D
[0202] A lithium ion secondary battery D was produced by the same procedure as in Example 4 except that the electrode A serving as the working electrode was changed to the electrode D. The capacity of the battery was 3 mAh.
[0203] [Comparative Example 8] Production of Lithium Ion Secondary Battery E
[0204] A lithium ion secondary battery E was prepared by the same procedure as in Example 4 except that the electrode A serving as the working electrode was changed to the electrode E. The capacity of the battery was 3 mAh.
[0205] [Comparative Example 9] Production of Lithium Ion Secondary Battery F
[0206] A lithium ion secondary battery F was produced by the same procedure as in Example 4 except that the electrode A serving as the working electrode was changed to the electrode F. The capacity of the battery was 3 mAh.
[0207] [Comparative Example 10] Production of Lithium Ion Secondary Battery G
[0208] A lithium ion secondary battery G was produced in the same manner as in Example 4 except that the electrode A serving as the working electrode was replaced by the electrode G. The capacity of the battery was 3 mAh.
[0209] [Comparative Example 11] Production of Lithium Ion Secondary Battery H
[0210] A lithium ion secondary battery H was produced by the same procedure as in Example 4 except that the electrode A serving as the working electrode was changed to the electrode H. The capacity of the battery was 3 mAh.
[0211] [Comparative Example 12] Production of Lithium Ion Secondary Battery I
[0212] A lithium ion secondary battery I was produced by the same procedure as in Example 4 except that the electrode A serving as the working electrode was changed to the electrode I. The capacity of the battery was 3 mAh.
[0213] The following evaluations were performed using the lithium ion secondary batteries A to I produced in Examples 4 to 6 and Comparative Examples 7 to 12.
[0214] (1) Rate characteristics
[0215] The lithium-ion secondary battery was placed in a thermostatic chamber at 25°C, the charge termination voltage was set to 3.0V, the discharge termination voltage was set to 1.0V, and 5 charge and discharge tests were performed continuously at a charge rate of 0.1C and a discharge rate of 0.1C. Then, 3 charge tests were performed continuously at a charge rate of 0.1C and a discharge rate of 5.0C. Furthermore, 3 charge and discharge tests were performed continuously at a charge rate of 0.1C and a discharge rate of 0.1C. A total of 11 charge and discharge tests were performed to determine the discharge capacity. The fifth discharge capacity and the eighth discharge capacity, as well as the ratio of the eighth discharge capacity to the fifth discharge capacity were selected as rate characteristics (%). These results are shown in Table 1. The unit of discharge capacity is mAh / g.
[0216]
Table 1
[0217]
[0218] (2) High temperature storage stability test (calendar life)
[0219] The prepared lithium-ion secondary battery was placed in a thermostatic chamber at 25°C, the charge termination voltage was set to 3.0V, the discharge termination voltage was set to 1.0V, and 5 charge and discharge tests were performed continuously under the conditions of a charge rate of 0.1C and a discharge rate of 0.1C. Then, only charging at a charge rate of 0.1C was performed. The charged non-aqueous electrolyte secondary battery was stored at 80°C for 10 days, and then 3 charge and discharge tests were performed under the conditions of a charge rate of 0.1C and a discharge rate of 0.1C. A total of 8 charge and discharge tests were performed to determine the discharge capacity. The fifth discharge capacity, the eighth discharge capacity, and the ratio of the eighth discharge capacity to the fifth discharge capacity were selected as the calendar life (%). These results are shown in Table 2. The unit of discharge capacity is mAh / g.
[0220]
Table 2
[0221]
[0222] From the results of Comparative Examples 7 to 12 shown in Tables 1 and 2, it can be seen that the lithium ion secondary battery with a different structure from the present invention cannot achieve both rate characteristics and calendar life at a high level. However, from the results of Examples 4 to 6, it can be confirmed that the lithium ion secondary battery of the present invention can achieve both rate characteristics and calendar life at a high level.
[0223] [Example 7] Fabrication of All-Solid Secondary Battery J
[0224] 25.0 parts by mass of SPAN prepared in Preparation Example 1 and lithium titanium oxide (Li4Ti5O 12 ) (manufactured by Ishihara Sangyo Co., Ltd., with an average secondary particle size of 7 μm), 25.0 parts by mass of acetylene black (manufactured by Denka Co., Ltd.) as a conductive aid, and 45.0 parts by mass of 75Li2S·25P2S5 (molar ratio of Li2S:P2S5 = 75:25) as a solid electrolyte were mixed and molded by pressing to produce a circular working electrode mixture layer with a diameter of 10 mm. Next, the layers were stacked in the order of SUS foil / working electrode mixture layer / solid electrolyte layer (75Li2S·25P2S5) / In-Li alloy / SUS foil, and the layers were pressed with a load of 20 kN and sealed in an all-solid-state battery evaluation unit (manufactured by Hohsen Co., Ltd., model KP-SolidCell), thereby producing an all-solid-state secondary battery J.
[0225] [Comparative Example 13] Production of All-Solid Secondary Battery K
[0226] An all-solid secondary battery K was produced by the same procedure as in Example 7 except that the electrode active material in Example 7 was changed to 50.0 parts by mass of SPAN produced in Production Example 1.
[0227] [Comparative Example 14] Production of All-Solid Secondary Battery L
[0228] The electrode active material in Example 7 was changed to only lithium titanium oxide (Li4Ti5O 12 An all-solid secondary battery L was manufactured by the same procedure as in Example 7 except that 50.0 parts by mass of ) (manufactured by Ishihara Sangyo Co., Ltd., average secondary particle size 7 μm) was added.
[0229] The following evaluations were performed using the all-solid secondary batteries J to L produced in Example 7, Comparative Example 13, and Comparative Example 14.
[0230] (1) Rate characteristics
[0231] The all-solid secondary battery was placed in a thermostatic chamber at 60°C, the charge termination voltage was set to 2.38V, the discharge termination voltage was set to 0.38V, and 5 charge and discharge tests were performed continuously under the conditions of a charge rate of 0.05C and a discharge rate of 0.05C, and then 3 charge and discharge tests were performed continuously under the conditions of a charge rate of 0.05C and a discharge rate of 1.0C, and a total of 8 charge and discharge tests were performed to determine the discharge capacity. The ratio of the eighth discharge capacity / fifth discharge capacity was calculated as the rate characteristic (%). These results are shown in Table 3.
[0232]
Table 3
[0233] All-solid-state secondary battery Rate characteristics [%] Example 7 All-solid secondary battery J 73 Comparative Example 13 All-solid secondary battery K 60 Comparative Example 14 All-solid secondary battery L 67
[0234] Description of Reference Numerals
[0235] 1 Positive electrode
[0236] 1a Positive electrode collector
[0237] 2 Negative electrode
[0238] 2a Negative electrode collector
[0239] 3 Non-aqueous electrolytes
[0240] 4. Positive electrode shell
[0241] 5. Negative electrode shell
[0242] 6 Gasket
[0243] 7 Separator
[0244] 10 Coin-type lithium-ion secondary battery
[0245] 10' cylindrical lithium ion secondary battery
[0246] 11 Negative electrode
[0247] 12 Negative electrode collector
[0248] 13. Positive electrode
[0249] 14. Positive electrode collector
[0250] 15 Non-aqueous electrolytes
[0251] 16 separator
[0252] 17 Positive terminal
[0253] 18 Negative terminal
[0254] 19 Negative plate
[0255] 20 Negative lead
[0256] 21. Positive plate
[0257] 22 Positive lead
[0258] 23 Shell
[0259] 24 Insulation board
[0260] 25 Gasket
[0261] 26 Safety valve
[0262] 27 PTC components
[0263] 28 Laminated lithium-ion secondary battery
[0264] 29 Electrode Group
[0265] 30 Shell side laminated film
[0266] 31 Cover side laminated film
Claims
1. An electrode having an active material layer formed on a current collector, wherein the active material layer contains sulfur-modified polyacrylonitrile and lithium titanium oxide, wherein: The average secondary particle size of the sulfur-modified polyacrylonitrile is 0.1 μm to 50 μm, and the average secondary particle size of the lithium titanium oxide is 0.05 μm to 30 μm. The average secondary particle size of the sulfur-modified polyacrylonitrile is greater than the average secondary particle size of the lithium titanium oxide. The content of the sulfur-modified polyacrylonitrile in the active material layer is 5% by mass to 85% by mass, and the content of the lithium titanium oxide in the active material layer is 5% by mass to 85% by mass.
2. A lithium-ion secondary battery comprising a positive electrode, a negative electrode, and a non-aqueous electrolyte containing a lithium salt, wherein: The positive electrode or the negative electrode is the electrode according to claim 1.
3. The lithium ion secondary battery according to claim 2, wherein: The non-aqueous electrolyte containing lithium salt is a liquid non-aqueous electrolyte.
4. The lithium ion secondary battery according to claim 2, wherein: The non-aqueous electrolyte containing lithium salt is a polymer gel non-aqueous electrolyte.
5. The lithium ion secondary battery according to claim 2, wherein: The non-aqueous electrolyte containing lithium salt is a polymer non-aqueous electrolyte.
6. The lithium ion secondary battery according to claim 2, wherein: The non-aqueous electrolyte containing a lithium salt is a complex hydride-based solid electrolyte.
7. The lithium ion secondary battery according to claim 2, wherein: The non-aqueous electrolyte containing lithium salt is an inorganic solid electrolyte.
8. The lithium ion secondary battery according to claim 3, wherein: The liquid nonaqueous electrolyte contains a cyclic carbonate compound.
9. The lithium ion secondary battery according to claim 8, wherein: The liquid nonaqueous electrolyte further contains a chain carbonate compound.
10. The lithium ion secondary battery according to claim 7, wherein: The inorganic solid electrolyte is a sulfide solid electrolyte or an oxide solid electrolyte.
Citation Information
Patent Citations
Carbon-coated active particles and process for their preparation
JP2019521488A
Sulfur-modified polyacrylonitrile, manufacturing method therefor, and application thereof
WO2010044437A1
Lithium-ion battery electrode material, lithium-ion capacitor electrode material, electrode, battery, capacitor, electric device, production method for lithium-ion battery electrode material, and production method for lithium-ion capacitor electrode material
CN111052467A
Lithium-ion battery electrode material, lithium-ion capacitor electrode material, electrode, battery, capacitor, electric device, production method for lithium-ion battery electrode material, and production method for lithium-ion capacitor electrode material
WO2019031208A1